2019
DOI: 10.1021/acs.analchem.8b05889
|View full text |Cite
|
Sign up to set email alerts
|

MicroLESA: Integrating Autofluorescence Microscopy, In Situ Micro-Digestions, and Liquid Extraction Surface Analysis for High Spatial Resolution Targeted Proteomic Studies

Abstract: The ability to target discrete features within tissue using liquid surface extractions enables the identification of proteins while maintaining the spatial integrity of the sample. Here, we present a *

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 90 publications
(158 reference statements)
0
58
0
Order By: Relevance
“…Previous in vitro studies have focused on the metabolic capabilities of S. aureus in the absence of glucose, as the centers of abscesses are predicted to be glucose-limited (21). Transcript and protein levels of gluconeogenic enzymes in S. aureus have also been found to be elevated during invasive infection, and in OM specifically (22,23). Our studies, however, suggest that S. aureus requires glycolysis and glycolytic carbon sources to survive in vivo during OM.…”
Section: Discussionmentioning
confidence: 58%
“…Previous in vitro studies have focused on the metabolic capabilities of S. aureus in the absence of glucose, as the centers of abscesses are predicted to be glucose-limited (21). Transcript and protein levels of gluconeogenic enzymes in S. aureus have also been found to be elevated during invasive infection, and in OM specifically (22,23). Our studies, however, suggest that S. aureus requires glycolysis and glycolytic carbon sources to survive in vivo during OM.…”
Section: Discussionmentioning
confidence: 58%
“…Label-free autofluorescence microscopy for functional and morphological tissue analyses is currently experiencing a true renaissance in life sciences, also driven by the rapidly developing techniques for image registration and mapping 22 and the capabilities of deep machine learning in detection, recognition and analysis of histo(morpho)logical patterns 48 . For correlation of MSI data with histomorphology, previous studies have already demonstrated the beneficial combination of autofluorescence microscopy with MALDI-MSI in multimodal analyses of (2D)-tissue sections 21 , 22 . Here, we used autofluorescence- and label-based LSFM, to define different regions of interest (ROIs) in optically cleared, 3-dimensional brain tissue samples for subsequent examination by MALDI-MSI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MALDI-MSI analyses can also be combined with a variety of other imaging modalities, providing additional morphological and/or biochemical information from the identical tissue section, or sample 14 , 17 . Previously reported multimodal (MALDI)-MSI analysis approaches e.g., include the combination with autofluorescence-microscopy 21 , 22 , Raman spectroscopy 23 , magnetic resonance imaging (MRI) 24 , 25 , histology, immunohistochemistry, and laser scanning confocal microscopy 26 . Using appropriate alignment methods 22 , 24 , 27 , the images acquired by MALDI-MSI and additional imaging modalities can be exactly overlaid and thus directly be related to e.g., distinct morphological features of the examined tissue, such as different structural compartments, cell types, pathological alterations, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Direct coupling to high-performance liquid chromatography for analyte separation and concentration prior to mass analysis is also possible and can be performed with commercial systems [18,21]. Recent bottom-up and top-down proteomics studies have been performed in this way and provide complementary data to conventional MSI experiments, with higher spatial resolution (∼110 μm) recently achieved with the microLESA setup [22][23][24]. Since the spatial resolution is largely governed by the available compatible pipette tips, modified systems demonstrating LESA at smaller sampling areas may be developed in the future.…”
Section: Liquid Extraction Surface Analysis (Lesa)mentioning
confidence: 99%